Why has there been a fall in child labour and an increase in school attendance in Mexico?. (5th July 2022) - Valero‐Gil, Jorge; Valero, Magali
Summary: Motivation: It is imperative to understand the factors affecting child labour and school attendance in order to develop policies aimed at improving children's lives. The need for such policies is because poor households may underinvest in human capital. Individual factors have been shown to affect child labour and school attendance, but we examine which factors cause the strongest effects by considering them simultaneously. Purpose: We evaluate the factors that have led to the changes in child labour and school attendance of children aged 12–14 in Mexico during the 2000–2020 period. We consider income, the education of the household head, government cash transfers, access to public health institutions, remittances, and demographic characteristics as possible sources of the changes. Methods and approach: We use a variant of the Oaxaca–Blinder decomposition, which allows decomposition when the variables to be explained are dichotomous. The change in child labour and school attendance over time can then be decomposed into explained and unexplained portions, with each factor contributing a specific amount to the explained portion of the change. Findings: The most important factor influencing improvements in child labour and school attendance was the improvement in the parents' human capital, measured as years of education. The result is not due to a high correlation between income and education, as significant explanatory power is lost as we exclude education from the analysis. The result is also robust to separating Mexican states into those with high and those with low incidence of poverty. The increase in government assistance and greater access to social health insurance also play an important role. Policy implications: Public policies aimed at increasing school attendance and those aimed at reducing child labour should consider improved education as a major goal. In addition, important consideration should be given to the possible impact on children of poverty‐fighting policy changes. Our findings suggest that government policies aimed at reducing poverty in Mexico are important in influencing both child labour and school attendance, and policy changes have had undesirable effects on both.